Inflation and macroeconomic variables : evidence from panel data - Ruphajivany, Sanjeven (2018)
Issues involving inflation has generated an enormous volume of literature and heated debate in recent years as different school of thoughts view the contrast cause and have different policies for fighting inflation. This study examines the relationship between selected independent variables and inflation and theory that can explain inflation in selected developed and developing countries of ASEAN and G7 countries using panel data analysis. The main variable of this study is money supply and unemployment. This study focus on the Quantity Theory of Money proposed by Irving Fisher and Phillips Curve. The issue that is brought forward is Keynesian’s argument that Fisher’s equation (MV=PT) is truism and only appropriate at full employment where it is impossible in the current situation. Hence, this employed study is to prove whether the Fisher’s equation is appropriate in the long-run or short-run. The argument of the Phillips Curve flattening is brought forward by authors, stating that the curve is appropriate in the short-run. Therefore, the motivation of this study is to prove that the Fisher’s Theory and the Phillips Curve is still appropriate in explaining inflationary problem. The empirical method to be employed are POLS regression, Granger Causality Test, Panel ARDL and Pooled Mean Group (PMG) estimation. The results from POLS regressions revealed that that money supply is significant to inflation (measured at CPI), and the Panel ARDL results indicate that the significance is for the long-run. There are two policy implications that is proposed in this study. First, the governments should put in place considerable reforms that will certify that the velocity of the supply of money in the market is constantly monitored and controlled. The central banks should also consider monetary policy as a suitable tool of achieving price stability because of the linear interdependency and causality between the price level and money supply growth. Second, the concerned policy makers as well as the government who are accountable for optimum level of inflation for sustainable growth and development should reduce the unemployment rate by opening more job opportunities for fresh graduates, although they are lack of job experience. This is to achieve the full employment rate in the economy.